Mapping of 3d eye-tracking in urban outdoor environments - Kollert, Andreas; Rutzinger, Martin; Bremer, Magnus; Kaufmann, Katja; Bork-Hüffer, Tabea (XXIV ISPRS Congress "Imaging today, foreseeing tomorrow", Commission IV, 2021)
New geospatial technologies and ubiquitous sensing allow new insights into people’s spatial practices and experiences of public spaces. These tools offer new data streams for analysis and interpretation of social phenomena. Mobile augmented reality tools such as smartphones and wearables merge the experience of entangled online and offline spaces in citizen’s daily life. This paper demonstrates a concept that combines eye-tracking tools with innovative mapping in order to enhance the interpretability of real outdoor environmental experiences. Through videogrammetry, a participants’ head posture can be reconstructed. Subsequently the fixations measured through eye-tracking are projected onto a 3D point cloud of the surrounding environment. The presented methodological approach is implemented in the interdisciplinary project DigitAS – The Digital, Affects and Space – which investigates the perception of public places as spaces of recreation, security or fear. The project’s Mixed Methods approach combined qualitative, mobile, in-situ and reconstructive methods with eye-tracking in an outdoor setting. Potentials of the geospatial mapping concept for social science research is discussed.